2014
DOI: 10.1002/jmri.24641
|View full text |Cite
|
Sign up to set email alerts
|

Age‐related differences in diffusion tensor indices and fiber architecture in the medial and lateral gastrocnemius

Abstract: Purpose To investigate age related changes in diffusion tensor indices and fiber architecture of the medial and lateral gastrocnemius (MG and LG) muscles using diffusion tensor imaging (DTI). Materials and Methods The lower leg of five young and five senior subjects was scanned at 3T and DTI indices extracted using three methods: ROI, histogram and tract based. Tracked fibers were automatically edited to ensure physiologically relevant tracks. Pennation angles were measured with respect to the deep and super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
63
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 33 publications
8
63
2
Order By: Relevance
“…In agreement with previous work that documented higher eigenvalues in women compared to men, our sample had higher mean k 1 , k 2 , and k 3 values at the TibA, SOL, MG, and LG, compared men [14]. Likewise, our findings are in line with a recent study that compared DTI measures in MG and LG of five young (mean age = 31.6 years) and five older (mean age = 83.4 years) Japanese women [15]. Sinha et al [15] reported higher eigenvalues in older women that were explained using a model that builds upon the existing interpretation of DTI measures [40,41].…”
Section: Discussionsupporting
confidence: 95%
See 4 more Smart Citations
“…In agreement with previous work that documented higher eigenvalues in women compared to men, our sample had higher mean k 1 , k 2 , and k 3 values at the TibA, SOL, MG, and LG, compared men [14]. Likewise, our findings are in line with a recent study that compared DTI measures in MG and LG of five young (mean age = 31.6 years) and five older (mean age = 83.4 years) Japanese women [15]. Sinha et al [15] reported higher eigenvalues in older women that were explained using a model that builds upon the existing interpretation of DTI measures [40,41].…”
Section: Discussionsupporting
confidence: 95%
“…Likewise, our findings are in line with a recent study that compared DTI measures in MG and LG of five young (mean age = 31.6 years) and five older (mean age = 83.4 years) Japanese women [15]. Sinha et al [15] reported higher eigenvalues in older women that were explained using a model that builds upon the existing interpretation of DTI measures [40,41]. Within the revised model, eigenvalues represent diffusion occurring in both intracellular and extracellular spaces [15].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations